Chest pain in the absence of obstructive coronary artery disease: A critical review of current concepts focusing on sex specificity, microcirculatory function, and clinical implications. (1st April 2019) - Zijlstra, Laurien E.; Bootsma, Marianne; Jukema, J. Wouter; Schalij, Martin J.; Vliegen, Hubert W.; Bruschke, Albert V.G.
Abstract: Patients presenting with chest pain suggestive of coronary artery disease (CAD) who at coronary arteriography appear to be free of obstructive disease have presented a diagnostic and therapeutic challenge since the 1970's. Studies in female patient populations have suggested that this is predominantly a women's syndrome usually caused by microvascular endothelial dependent and independent dysfunction. A critical review of the literature focusing on studies including both women and men revealed that apart from a higher incidence of this syndrome in women there are no clinical relevant differences between both sexes. In women a lower coronary flow reserve has been reported but this appears to be mainly due to a higher basal flow. Important questions with regard to the clinical implications of microvascular dysfunction have yet to be resolved in studies involving women as well as men in which a distinction is made between patients with normal coronary arteries and those with nonobstructive disease. Highlights: Sex specificity of microvascular angina has not been proven. Women more often than men have chest pain without coronary obstructions. Hypertension is a common cause of microvascular disease and in part reversible. Irrespective of sex normal coronary arteries indicates a favorable prognosis.